Model Penguatan Perlindungan Kekayaan Intelektual Komunal: Transplantasi Muatan Kebijakan Termasuk Benefit-Sharing Berbasis Undang-Undang - Ni Ketut Supasti Dharmawan; Putu Aras Samsithawrati; Desak Putu Dewi Kasih; Putri Triari Dwijayanthi; I Gede Agus Kurniawan (Jurnal Ilmiah Kebijakan Hukum, 2023)
Regulations regarding the protection of communal intellectual property in Indonesia are currently scattered in various regulations that are not explicitly stated in the form of Laws, and do not regulate benefit-sharing comprehensively. The purpose of this research is to elaborate on a protection strengthening model of Communal Intellectual Property based on the transplantation of policy content related to works of tradition, culture, custom, traditional knowledge, genetic resources and potential geographical indications from various existing legal policies and other sources both locally, nationally and internationally into the legal form of a Law, as well as a benefit-sharing regulation mechanism related to the commercial use of Communal Intellectual Property. The research method used is normative legal research with statutory, comparative, conceptual and analytical approaches. The results of the research showed that the current policy regarding Communal Intellectual Property in Indonesia is still in the hierarchy of Regulations of the Minister of Law and Human Rights and Government Regulations, namely Permenkumham 13/2017 and PP 56 of 2022. Several articles in the provisions of statutory regulations on Intellectual Property in Indonesia have regulated Communal Intellectual Property, but its nature is still very general. For stronger protection and legal certainty it is very urgent to regulate the protection policy in the form of a Law through a transplantation model of the substance of existing legal products related to Communal Intellectual Property, as well as strengthening of policy content including benefit-sharing in relation to the commercial use of Communal Intellectual Property.